A second-order nonlinear optical crystal material of ammonium zinc thiocyanate and its preparation and application
By developing second-order nonlinear optical crystal materials of zinc ammonium thiocyanate, the shortcomings of existing NLO materials in ultraviolet optical performance and frequency multiplication response are solved, and high-performance nonlinear optical effects are achieved, which are suitable for a variety of optical applications.
Patent Information
- Application Number
- CN202411071186.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-08-06
AI Technical Summary
现有非线性光学(NLO)晶体材料在紫外光学性能和倍频响应方面存在不足,难以满足高性能NLO材料的需求。
A second-order nonlinear optical crystal material of zinc ammonium thiocyanate is developed, with the chemical formula of (NH4)2Zn(SCN)4·3H2O. Through a reasonable design structure, its linear and nonlinear optical properties are enhanced and prepared by solution evaporation.
The crystal material exhibits strong powder frequency multiplication response, suitable birefringence and large optical band gap, and the frequency multiplication signal intensity reaches 8 times that of KDP crystals. It is suitable for applications such as frequency multiplication generators and laser frequency converters.
Smart Images

Figure CN119065174B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to an ammonium zinc thiocyanate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art
[0002] Nonlinear optical (NLO) crystals play an important role in laser science and technology and can be used in short-wave communications, laser engraving, high-density storage, medical diagnosis, and precision instrument processing. Creating new ultraviolet NLO materials is the focus and difficulty of current research. Currently commercialized NLO crystals include β-BaB 2 O 4 (BBO), KBeBO 3 F 2 (KBBF), LiB 3 O 5 (LBO) and KH 2 PO 4 (KDP), etc. Although the above crystals have excellent comprehensive properties, with the development of society and the continuous expansion of application fields, the requirements for NLO crystal materials are getting higher and higher, and the development of high-performance NLO crystal materials is extremely urgent.
[0003] Thiocyanate is an important NLO material system because of the presence of lone electron pairs on sulfur (S) and nitrogen (N) in its structure and its strong polarizability. There are few reports on crystals that combine strong SHG, large band gap and suitable birefringence properties in the thiocyanate system. Therefore, it is crucial to further synthesize thiocyanate-based NLO crystal materials with excellent comprehensive properties through rational design. Summary of the invention
[0004] The purpose of the present invention is to provide a second-order nonlinear optical crystal material of ammonium zinc thiocyanate and its preparation and application. Its linear SCN group greatly enhances the linear and nonlinear optical properties of ammonium zinc thiocyanate, and exhibits a strong powder double frequency response (8×KDP), a suitable birefringence (0.185@546nm) and a large optical band gap (4.18eV).
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In one aspect, the present invention provides a second-order nonlinear optical crystal material of zinc ammonium thiocyanate, whose chemical formula is (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O, molecular weight is 387.82, belongs to the orthorhombic system, and its space group is P2 1 2 12, the unit cell parameters are α=β=γ=90°, Z=2, the unit cell volume is
[0007] Furthermore, the crystalline material contains isolated [Zn(SCN) 4 ] group.
[0008] Further, the chemical formula of the crystalline material is (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O, molecular weight is 387.82, belongs to the orthorhombic system, and its space group is P2 1 2 1 2, the unit cell parameters are α=β=γ=90°, Z=2. Further preferably, the unit cell parameters are α=β=γ=90°, Z=2. Most preferably, the unit cell parameters are α=β=γ=90°, Z=2.
[0009] The crystal structure of ammonium zinc thiocyanate of the present invention is as follows Figure 1 As shown. (NH 4 ) 2 Zn(SCN) 4 ·3H 2 The structure of O consists of discrete [Zn(SCN) 4 ] structural unit, NH 4 + Cations and H 2 O molecular composition. Zn 2+ The cation is coordinated with four N atoms from four [SCN] units to form a [Zn(SCN) 4 ] structural unit, [Zn(SCN) 4 ] structural unit and NH 4 + Cations and H 2 O molecules are connected by hydrogen bonds.
[0010] On the other hand, the present invention also provides a method for preparing zinc ammonium thiocyanate second-order nonlinear optical crystal material, which comprises weighing a soluble zinc source, a soluble ammonium thiocyanate source and water, mixing them, stirring to obtain a clear and transparent solution, and volatilizing to obtain colorless and transparent rod-shaped crystals, which are the target product. The ratio of the zinc source to the ammonium thiocyanate source and the reaction temperature are the preparation (NH 4 ) 2 Zn(SCN) 4 ·3H 2 The key factor of O.
[0011] Furthermore, the soluble zinc source is zinc nitrate hexahydrate.
[0012] Furthermore, the ammonium thiocyanate source is ammonium thiocyanate.
[0013] Furthermore, the added amounts of the soluble zinc source and the ammonium thiocyanate source satisfy: the molar ratio of the Zn element to the S element is between 2:3 and 5:11, and the amount of the ammonium thiocyanate source used is greater than the amount of the zinc source.
[0014] Furthermore, the volatilization temperature of the solution is 5 to 35° C., more preferably 15 to 25° C., and the volatilization time is not less than one week, more preferably not less than two weeks.
[0015] According to the hard-soft acid-base theory, thiocyanate is a boundary acid, which can react with Zn through N and S. 2+ Form coordination bonds, or S and NH 4 + and H 2 O forms hydrogen bonds. The diversity of these two bonding modes leads to two competitive reactions in the solution after the thiocyanate source and the zinc source are dissolved in deionized water:
[0016] Zn 2+ + 2SCN - = Zn(SCN) 2 (1)
[0017] 2NH 4 + + Zn 2+ + 4SCN - + 3H 2 O = (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O (2)
[0018] When Zn in solution 2+ When the concentration of SCN is equal to or slightly greater than that of SCN (the ratio between the two is between 3:2 and 1:1), and the solution temperature is high (temperature range is between 35 and 45 °C), S and Zn 2+ The covalent coordination of S is stronger than that of NH 4 + and H 2 O, and then (1) reaction occurs; when Zn 2+ When the concentration is lower than that of SCN (the ratio between them is between 2:3 and 2:5) and the solution temperature is low (temperature range is between 15 and 25°C), S and Zn 2+ The coordination bonding effect of S is weaker than that of NH4 + and H 2 O bonding, and reaction (2) occurs. The reactant ratio and temperature range used in the present invention are consistent with the situation where reaction (2) occurs, so the prepared crystal is pure (NH 4 ) 2 Zn(SCN) 4 ·3H 2 ORod-shaped crystals.
[0019] In a third aspect, the present invention provides an application of an ammonium zinc thiocyanate second-order nonlinear optical crystal material in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
[0020] In a fourth aspect, the present invention provides an application of an ammonium zinc thiocyanate second-order nonlinear optical crystal material, which is used in a laser frequency converter and outputs 532nm green light under 1064nm laser irradiation.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) This application provides a new nonlinear optical crystal (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O, the crystal material has a large frequency doubling effect, which is about 8 times the frequency doubling intensity of KDP crystal under 1064nm laser irradiation, and can achieve phase matching. In addition, the crystal material has high optical transmittance in the ultraviolet, visible and near-infrared light range, and its optical band gap is 4.18eV. Therefore, the crystal material has broad application prospects in the field of nonlinear optics.
[0023] (2) The present application also provides the nonlinear optical crystal (NH 4 ) 2 Zn(SCN) 4 ·3H 2 The preparation method of O is to use the solution evaporation method to grow a colorless (NH 4 ) 2 Zn(SCN) 4 ·3H 2 The method is simple in process and mild in conditions, and is easy to grow single crystals with high optical quality and high purity.
[0024] (3) The ammonium zinc thiocyanate crystal material of the present invention can be applied to a laser frequency converter, and can be used to output a laser beam as a double frequency harmonic. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1It is a schematic diagram of the crystal structure of ammonium zinc thiocyanate;
[0026] Figure 2 This is a crystal photo of ammonium zinc thiocyanate;
[0027] Figure 3 The X-ray diffraction pattern of sample 1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder;
[0028] Figure 4 is the UV-Vis-NIR diffuse reflectance spectrum of sample 1#;
[0029] Figure 5 is the infrared spectrum of sample 1#;
[0030] Figure 6 This is the thermogravimetric analysis spectrum of sample 1#;
[0031] Figure 7 This is the birefringence test chart of sample 1#;
[0032] Figure 8 It is the second harmonic signal diagram of sample 1# and KDP sample with size ranging from 105 to 150 μm;
[0033] Fig. 9 This is the second harmonic phase matching diagram of sample 1# in the 1064nm band. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0035] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0036] Embodiment 1:
[0037] Preparation of samples 1# to 8#
[0038] Mix the zinc source, ammonium thiocyanate source and water in a certain proportion to form a raw material, place it in a glass beaker and stir it continuously until a clear and transparent solution is obtained. By slowly evaporating at room temperature, a colorless and transparent (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O crystal.
[0039] The relationship between the type and ratio of raw materials in the initial mixture, the volatilization temperature, the volatilization time and the sample number is shown in Table 1.
[0040] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0041]
[0042]
[0043] Crystal structure analysis of samples 1# to 8#
[0044] The structure and phase analysis of samples 1# to 8# were carried out using single crystal X-ray diffraction and powder X-ray diffraction methods.
[0045] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of atoms were determined using the direct method, and the F-based 2 The coordinates of all atoms and anisotropic thermal parameters were refined by full matrix least squares. All atoms were refined using anisotropic displacement parameters, and the absolute structure was checked using PLATON to find no missing symmetry elements.
[0046] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu-Kα, a wavelength The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.
[0047] Among them, the single crystal X-ray diffraction results show that samples 1#~8# have the same chemical formula and crystal structure, and the chemical formula is (NH 4 ) 2 Zn(SCN) 4 ·3H 2 O, belongs to the orthorhombic system, its space group is P2 1 2 1 2, the unit cell parameters are α=β=γ=90°, Z=2.
[0048] Take sample 1# as a typical example, its crystal structure data is α=β=γ=90°, Z=2. Its crystal structure is as follows Figure 1 shown.
[0049] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 8#, the peak positions of each sample are basically the same, but the peak intensities are different.
[0050] Take sample 1# as a typical example. Figure 2 As shown, according to the crystal structure analyzed by its single crystal X-ray diffraction, the fitted X-ray diffraction pattern is consistent with the diffraction peak position of the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, indicating that the obtained sample has high purity.
[0051] UV-Visible Near Infrared Diffuse Reflectance Spectroscopy Test
[0052] The diffuse reflectance spectrum test of sample 1# was conducted on a LAMBDA 1050+ UV-Vis-NIR spectrometer from PerkinElmer, USA. The results are shown in Figure 3 As shown by Figure 3 The compound has good transmission in the ultraviolet and visible light bands, and its optical band gap is 4.18 eV.
[0053] Infrared spectrum test
[0054] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown, it is proved that the crystal material contains SCN anion groups, NH 4 + Cations and water molecules. The characteristic peak of the SCN anion group is at 2075cm -1 The characteristic peak of water molecules is at 3222cm -1 1418 and 1604 cm -1 The peak at 4 + The peaks of cations and water molecules overlap.
[0055] Thermogravimetric testing
[0056] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 6 As shown by Figure 6 It can be seen that the thermal decomposition temperature of the compound is 30°C.
[0057] Birefringence test
[0058] The birefringence test of sample 1# was conducted on an Axioscope A1 polarizing microscope equipped with a Berek compensator from Zeiss, Germany, with a light source wavelength of 546nm. The birefringence can be calculated using the formula:
[0059] ΔR(delay)=|n e -n o | × T=Δn × T (3)
[0060] ΔR represents the optical path difference, Δn represents the birefringence, and T is the thickness of the crystal. The test results are as follows Figure 7 As shown, the crystal optical path difference is 2.912 μm, the crystal thickness is 15.724 μm, and the birefringence measurement value is calculated to be 0.185.
[0061] Frequency doubling test experiment and results
[0062] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a photomultiplier tube is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the control sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve. The particle size ranges are less than 26, 26-50, 50-74, 74-105, 105-150, and 150-200μm, respectively. Observe the trend of the frequency doubling signal intensity changing with the particle size to determine whether phase matching can be achieved. Under the same test conditions, the second harmonic intensity generated by the sample and the KDP sample is compared to obtain the relative size of the sample frequency doubling effect.
[0063] The test results show that the compound ammonium zinc thiocyanate crystal has a large frequency doubling effect. Under 1064nm wavelength laser irradiation, the frequency doubling signal intensity is 8 times that of the control sample KDP crystal (such as Figure 8 ), phase matching can be achieved (such as Fig. 9 ).
[0064] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A zinc ammonium thiocyanate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is (NH4)2Zn(SCN)4·3H2O, it belongs to the orthorhombic system, its space group is P21212, and its unit cell parameters are α=β=γ=90°, Z=2, the unit cell volume is 2. The ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 1, characterized in that: Contains isolated [Zn(SCN)4] groups.
3. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: Weigh a soluble zinc source, a soluble ammonium thiocyanate source and water, mix them, stir to obtain a clear and transparent solution, evaporate, and obtain colorless and transparent rod-shaped crystals, which are the target product.
4. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The soluble zinc source is zinc nitrate hexahydrate.
5. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The ammonium thiocyanate source is ammonium thiocyanate.
6. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The added amounts of the soluble zinc source and the ammonium thiocyanate source satisfy that the molar ratio of the Zn element to the S element is 2:3 to 5:
11.
7. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The volatilization temperature is 15-25°C.
8. The method for preparing the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 3, characterized in that: The volatilization time is not less than one week.
9. Use of the ammonium zinc thiocyanate second-order nonlinear optical crystal material as claimed in claim 1 or 2 in a frequency doubling generator, an optical parametric oscillator, an optical parametric amplifier and a photoelectric rectifier.
10. Use of the ammonium zinc thiocyanate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: It is used in laser frequency converters and outputs 532nm green light under 1064nm laser irradiation.